Effect of Different Pressure Treatment Methods on Dimensional Stabilization of Chemically Modified Pinus radiata Wood - Hom, Sanjeet Kumar; Poonia, Pawan Kumar; Samani, Ajmal; Tripathi, Sadhna (Indian Forester, 2016)
Wood is dimensionally unstable and hygroscopic in nature due to presence of large number of hydroxyl groups in the polymeric constituents. Chemical modification is one way of improving this property and acetylation provides dimensional stability to wood, due to cell wall bulking. In the present study Pinus radiata wood samples were modified with pyridine catalyzed acetic anhydride by combination of pressure and heat treatment for different time periods. Weight Percentage Gain, Volumetric Swelling Coefficient and Anti-Swelling Efficiency were determined. Samples were immersed in waterfora time period of 1hr to 120hrs to calculate Volumetric Swelling Coefficient and Anti-Swelling Efficiency for estimating dimensional stability. Schedule of applying pressure of 20lbs per inch2 at 120 Â°C for 1hr showed maximum dimensional stability.